2022
DOI: 10.1136/bcr-2022-252848
|View full text |Cite
|
Sign up to set email alerts
|

Novel use of metallic stent to control post-debulking bleeding in a patient with central airway obstruction

Abstract: Bronchoscopy-related bleeding is often encountered and is usually self-limiting or controllable by conservative measures. However, major bleeds can be life threatening for the patient as well as challenging for the physician to manage. There are several methods to achieve adequate haemostasis should a significant airway bleed occur. In this context, we describe a patient who had a post-bronchoscopic debulking bleed which persisted despite use of all available measures, and we deployed a self-expanding metallic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…There are no objective criteria for when to remove stents. A study done in 2013 in Seoul, South Korea showed that patients stented for more than 12 months had a significantly lower restenosis rate than those with stents for less than 12 months 18 19. Our patient, being an adult man with post-traumatic tracheal stenosis, showed good response to silicone stenting and underwent removal at 2 months, is currently asymptomatic and in regular follow-up.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…There are no objective criteria for when to remove stents. A study done in 2013 in Seoul, South Korea showed that patients stented for more than 12 months had a significantly lower restenosis rate than those with stents for less than 12 months 18 19. Our patient, being an adult man with post-traumatic tracheal stenosis, showed good response to silicone stenting and underwent removal at 2 months, is currently asymptomatic and in regular follow-up.…”
Section: Discussionmentioning
confidence: 56%
“…Stent-related complications include stent migration which may lead to tracheobronchial occlusion, secondary infection due to retention of secretions, stent blockade due to granulation tissue formation, airway erosion and bleeding 18. Other less known complications are stent fracture, difficulty in removal of stent and epithelialisation around the stent.…”
Section: Discussionmentioning
confidence: 99%
“…Stent placement has also been used to control airway bleeding. When stenting is needed for this indication, it is often in the setting of diffuse bleeding from large areas of airway tumor involvement [22]. In such a scenario, a stent can tamponade a large area of bleeding mucosa to achieve hemostasis more quickly than standard bronchoscopic interventions for bleeding.…”
Section: Indications For Stent Placementmentioning
confidence: 99%
“…A much less common indication for stenting is when bleeding control with tamponade of an airway wall is needed. This has been typically done in the setting of diffuse airway wall bleeding such as due to tumor infiltration ( 4 ). Endoluminal ablative therapies can be used but a stent is a rapid intervention that can cover a wide area of disease relatively quickly.…”
Section: Indicationsmentioning
confidence: 99%